An HST Transmission Spectrum of the Closest M Dwarf Transiting Rocky Planet LTT 1445Ab - Katherine A. Bennett; David K. Sing; Kevin B. Stevenson; Hannah R. Wakeford; Zafar Rustamkulov; Natalie H. Allen; Joshua D. Lothringer; Ryan J. MacDonald; Nathan J. Mayne; Guangwei Fu (The Astronomical Journal)
Which rocky exoplanets have atmospheres? This presumably simple question is the first that must be answered to understand the prevalence of nearby habitable planets. A mere 6.9 pc from Earth, LTT 1445A is the closest transiting M dwarf system, and its largest known planet, at 1.31 R _⊕ and 424 K, is one of the most promising targets in which to search for an atmosphere. We use Hubble Space Telescope/Wide Field Camera 3 transmission spectroscopy with the G280 and G141 grisms to study the spectrum of LTT 1445Ab between 0.2 and 1.65 μ m. In doing so, we uncover an ultraviolet (UV) flare on the neighboring star LTT 1445C that is completely invisible at optical wavelengths; we report one of the first simultaneous near-UV/optical spectra of an M dwarf flare. The planet spectrum is consistent with a flat line (with median transit depth uncertainties of 128 and 52 ppm for the G280 and G141 observations, respectively), though the infrared (IR) portion displays potential features that could be explained by known opacity sources such as HCN. Some atmospheric retrievals weakly favor (∼2 σ ) an atmosphere, but it remains challenging to discern between stellar contamination, an atmosphere, and a featureless spectrum at this time. We do, however, confidently rule out ≤100× solar metallicity atmospheres. Although stellar contamination retrievals cannot fit the IR features well, the overall spectrum is consistent with stellar contamination from hot or cold spots. Based on the UV/optical data, we place limits on the extent of stellar variability expected in the near-IR (30–40 ppm), which will be critical for future James Webb Space Telescope observations.